A Note on the Economic Cost of Climate Change and the Rationale to Limit it Below 2°C - Hallegatte, Stephane (World Bank, Washington, DC, 2014)
This note highlights a major reason to limit climate change to the lowest possible levels. This reason follows from the large increase in uncertainty associated with high levels of warming. This uncertainty arises from three sources: the change in climate itself, the change s impacts at the sector level, and their macroeconomic costs. First, the greater the difference between the future climate and the current one, the more difficult it is to predict how local climates will evolve, making it more difficult to anticipate adaptation actions. Second, the adaptive capacity of various economic sectors can already be observed for limited warming, but is largely unknown for larger changes. The larger the change in climate, therefore, the more uncertain is the final impact on economic sectors. Third, economic systems can efficiently cope with sectoral losses, but macroeconomic-level adaptive capacity is difficult to assess, especially when it involves more than marginal economic changes and when structural economic shifts are required. In particular, these shifts are difficult to model and involve thresholds beyond which the total macroeconomic cost would rise rapidly. The existence of such thresholds is supported by past experiences, including economic disruptions caused by natural disasters, observed difficulties funding needed infrastructure, and regional crises due to rapid economic shifts induced by new technologies or globalization. As a consequence, larger warming is associated with higher cost, but also with larger uncertainty about the cost. Because this uncertainty translates into risks and makes it more difficult to implement adaptation strategies, it represents an additional motive to mitigate climate change.